Heterogeneity, spillovers and eco-efficiency of European industries under different pollutants’ scenarios. Is there a definite direction? - Stergiou, Eirini; Kounetas, Konstantinos (Ecological economics, 2022)
•Evaluation of industrial eco-efficiency across Europe.•Scenarios affect the mitigation of emissions differently and the disposal of undesirable outputs becomes a costly activity.•Technological spillovers have led to progression toward the best technology.•Significant long run differences persist in terms of convergence.•Emissions per capita have been decreased in the 1995–2011 period in Europe. Eco-efficiency is the ability to create more goods and services with less impact on the environment while it consists a dominant strategy for the European Union in view of the New Green Deal. In recent years, its assessment, especially for the manufacturing sector, has attracted the interest of policymakers as a strategy in the pursuit of sustainability. However, a clear-cut direction on which industries should follow does not exist. In this applied study, we estimate distinct objectives of economic and ecological performance, introducing diverse scenarios regarding specific environmental pressures, by utilizing directional distance functions under a metafrontier framework. The methodology is implemented to a sample of 14 industries from the manufacturing sector from 27 European countries over the period 1995–2011. Our results reveal that the existence of a unified production technology set causes large differences in the eco-efficiency levels of the manufacturing sector while energy intensive industries can be characterized as the most eco-inefficient. Although the speed of industrial eco-efficiency convergence increases throughout the years, the case of CO2 emissions presents an irregular behavior compared to the other greenhouse gases and air pollutants. Thus, a decomposition analysis of the manufacturing CO2 emissions is considered as a further subject of interest in the study.